Uptake and utilization of nitrogen applied to the foliage of winter wheat - Hopkinson, Jill (1998)
Foliar urea was applied as a source of late-N between flag leaf emergence and anthesis to winter wheat crops that had received varying rates of basal-N fertilizer in the spring in order to produce crops with differently sized GAI). The crops grown were: no N fertilizer applied (NO), conventionally fertilized (Net), a Canopy Managed crop grown to a GAI 5 (GAI 5), at IACR-Rothamsted in 1995, with the addition of a GAI 3 crop (GAI 3) at IACR-Rothamsted in 1994 and at Sutton Bonington in 1995.